IMPLEMENTATION OF ANTI-CORRUPTION POLICY OF UKRAINE IN THE CONTEXT OF ENSURING STATE SECURITY - Sokyrko , Serhii (Global Prosperity, 2023)
The article analyzes the implementation of the anti-corruption policy of Ukraine, which is based on the provisions of the Anti-Corruption Strategy for 2021-2025 in the context of ensuring the state security of Ukraine. It is shown that instability in the state, conflicts, and corruption are closely interrelated. Corruption is closely related to state security. Theoretical studies have described in detail such a connection between corruption and conflicts, as well as corruption and political instability. It was determined that the Anti-Corruption Strategy of Ukraine for 2021-2025 was developed taking into account the interests of all stakeholders in combating corruption. This became possible on the basis of a significant number of consultations with the public, experts, and representatives of the business environment. It has been established that, in terms of its focus, this strategy involves optimizing the functions of state authorities and local self-government, in particular regarding the prevention of duplication of powers among; implementation of digital transformation of the activities of authorities at the national and local levels; ensuring transparency and openness of data; development of law-adaptive ways of meeting the relevant needs of people; the use of norms regarding unavoidable legal responsibility for manifestations of corruption; stimulating the negative attitude of society towards corruption. Judicial and law enforcement agencies are the priority spheres of corruption prevention; land relations and construction; taxation and customs affairs; health care; state regulation of Economy; Social Protection. The results of the Ministry of Defense of Ukraine regarding the implementation of anti-corruption policy measures require special attention. According to the results of the analysis and assessment of data in the mass media in 2021, which related to anti-corruption topics in the Ministry of Defense of Ukraine, 299 messages were found that were characterized by a negative tone. In anti-corruption reports, the information mainly concerned: phenomena of corruption and dishonesty of officials in the implementation of construction and procurement; procurement at the highest prices of low-quality samples of military equipment and weapons, equipment and medical drugs; receipt of illegal remuneration by individual officials; abuse of official position, illegal acquisition of land plots. Such information formed the basis for the implementation in the Ministry of Defense of Ukraine of mechanisms aimed at reducing corruption risks, as well as eliminating the conditions for violations of anti-corruption legislation